An Analysis on Carbon Credits in Indian Perspective (International Journal of Food and Nutritional Sciences, 2022)
The rising cost of fossil fuels is a major concern. It not only means these resources arebecoming scarcer but also highlights the damage they cause to our environment, especiallythrough increased greenhouse gas emissions. As a result, there's a growing interest in findingand developing alternative energy sources that are clean and renewable. Renewable energy isnow being viewed as a preferable option compared to nuclear power, which poses risks ofsignificant disasters. Carbon dioxide, a major greenhouse gas, traps heat that would otherwiseescape into space, leading to worldwide heating. There is a worldwide push to reduceemissions of carbon, with one of key strategies being the use of Carbon Credits. This concept,derived from the Kyoto Protocol, aims to regulate greenhouse gas emissions by allowing thetrading of carbon credits among countries and governments. This paper will explore carboncredits as an alternative approach to reducing emissions of carbon.